The international survey on the management of allergic rhinitis by physicians and patients (ISMAR) - Baena Cagnani, Carlos E. (2015)
Epidemiologic studies suggest that the prevalence of allergic rhinitis (AR) is rising worldwide. Several reports, in fact, indicate increasing trends in the prevalence of AR especially in developing countries, likely related to the environment and climate changes and the adoption of an urbanized Western lifestyle. The primary objective of the present study was to collect information about management in real-life settings, including a characterization of typical patients’ profile referring to physicians, the disease features, the common approaches to diagnostic assessments and therapeutic decisions. This was an international, multicenter, cross-sectional study conducted in adults or children (≥6 years) suffering from rhinitis confirmed by physician's diagnosis for at least one year. The 234 physicians who participated in the study included a total of 2778 patients in Egypt, Mexico, Brazil, Colombia, Guatemala, Iran, Venezuela, Argentina, Israel, Kuwait and United Arab Emirates. It was found that clinical history was the selected tool to diagnose and categorize AR patients (97.1%), with less than half of patients undergoing allergy testing, may be explaining the scarce use of immunotherapy on management of disease. Out of 2776 patients, 93.4% had somehow received a recommendation to avoid allergens and irritant agent exposure. Notably, 91.4% were receiving at least one treatment at the time of the survey, mostly oral antihistamines (79.7%) and intranasal corticosteroids (66.3%). Oral antihistamines, intranasal steroids and decongestants were considered both safe and effective by patients and physicians, preferring oral and nasal route of administration. The ISMAR registry was designed according to the most accepted epidemiological recommendations, and provides interesting information regarding the management of rhinitis from a patient and physician points of view, with many similarities between the participating countries. Further efforts are required to better manage AR and its comorbidities.